First: multiply the 1st & 3rd coefficient to get "72." Find two numbers that give you "72" when multiplied & "18" (2nd/middle coefficient) when added/subtracted. The numbers are (6 & 12).
Sec: rewrite the expression with the new middle coefficients...
8x^2 + 6x + 12x + 9
Third: when you have 4 terms - group "like" terms & factor....
(8x^2 + 6x) + (12x + 9)
2x(4x + 3) + 3(4x + 3)
= (4x + 3 )(2x + 3)
2007-02-02 14:10:27
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
The factors of 8x^2+18x+9 are 4x+3 and 2x+3
2007-02-02 22:19:57
·
answer #2
·
answered by dennismeng90 6
·
0⤊
0⤋
We need factors of 8•9 = 72 that add up to 18, and they are 6 and 12, so
8x² + 18x + 9 =
8x² + 6x + 12x + 9 =
2x( 4x + 3) + 3( 4x + 3) =
(2x + 3)( 4x + 3)
2007-02-02 22:10:16
·
answer #3
·
answered by Philo 7
·
0⤊
0⤋
Given expression
=8x^2+12x+6x+9
=4x(2x+3)+3(2x+3)
=(2x+3)(4x+3)
2007-02-02 22:04:40
·
answer #4
·
answered by alpha 7
·
0⤊
1⤋
= 8x^2 + 12x +6x +9
= 4x ( 2x + 3 ) + 3 (2x + 3 )
= ( 2x + 3 ) ( 4X + 3 )
2007-02-02 22:04:33
·
answer #5
·
answered by sg 2
·
0⤊
1⤋
You can do this with the quadratic equation, but I'll do it:
(4x+3)(2x+3)
2007-02-02 22:05:28
·
answer #6
·
answered by John T 6
·
0⤊
1⤋
(4x + 3) (2x + 3)
2007-02-02 22:04:49
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋